HERMENEUTIKA AL-QUR’AN MUHAMMAD AL-GHAZALI (Telaah Metodologis atas Kitab Nahwa Tafsir Maudhu’i li Suwar al-Qur’an al-Karim) - Nadhirah, Wardah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2016)
This article elaborates al-Ghazali ideas on the qur’anic hermeneutical concept. The author concludes that al-Ghazali’s qur’anic hermeneutical concept has similarities with the theory of philosophical hermeneutics initiated by Gadamer in practice. It can be understood from the various interpretations expressed in the book Nahwa Maud}ū’i Tafsir al-Qur’an li Suwar al-Karīm. But even so, one thing that is emphasized by Muhammad al-Ghazali in his interpretation of the Qur’an that the Quran is a unified whole that must be understood in the context of a whole.